Antecedent and Consequences of Customerelight: A Study at Fine Dining Restaurant in Indonesia - Aryani, Budi; Djasfar, Farida; Kristaung, Robert; Warsinda, Lucy (Green Publisher Indonesia, 2022)
This study is to analyze the role of customer delight in mediating the effect of experiential value on Word of Mouth (WOM) on customers of fine dining restaurants in Indonesia. Questionnaires were distributed using purposive sampling technique in order to obtain a sample of 250 respondents. The research data were analyzed statistically descriptive using the Partial Least Square (PLS) method. The results of the study found that experiential value variables supported by the dimensions of customer escapism, food and beverage excellence and customer efficiency showed a positive influence on customer delight and on WOM. The experiential value variable which is supported by the dimensions of food and beverage excellence has an effect on WOM if mediated by customer delight variable , experiential value variable which is supported by customer escapism dimension also affects WOM when mediated by customer delight variable. The originality of this research lies in the experiential value variable with dimensions of aesthetic experience, and service excellence turns out to have an effect on customer delight or on WOM, customer delight as a mediating variable has no effect on the dimensions of aesthetic experience, service excellence and customer efficiency on WOM. This research is limited only to fine dining restaurants. The managerial implication of this research is that experiential value can be increased through the beautiful appearance of food and beverage excellence accompanied by the appropriate temperature, the customer escapism strategy can be an attractive service alternative if it is equipped with a delightful touch.